2019
DOI: 10.1038/s41598-019-52433-w
|View full text |Cite|
|
Sign up to set email alerts
|

Phonological network fluency identifies phonological restructuring through mental search

Abstract: We investigated network principles underlying mental search through a novel phonological verbal fluency task. Post exclusion, 95 native-language Mandarin speakers produced as many items that differed by a single lexical tone as possible within one minute. Their verbal productions were assessed according to several novel graded fluency measures, and network science measures that accounted for the structure, cohesion and interconnectedness of lexical items. A multivariate regression analysis of our participants’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 111 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…Empirical and theoretical research in the cognitive sciences identified these mental representations of knowledge as components of a way more complex system called mental lexicon, a repository of knowledge apt at information acquisition, processing, and use [21]. The recent adoption of network science tools has shown how the large-scale, associative structure of word knowledge in the mental lexicon is highly informative of a wide variety of cognitive processes such as lexical processing [19,22,23,24], learning and cognitive development [25,26,27], text structuring and writing styles [28,29,30,31], creativity [32,33], and expertise levels in specific domains [34,5]. Analogously, forma mentis networks act as approximated reconstructions on the mental constructs built by individuals in their associative mental lexicon, representing their perceptions of the outer world [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical and theoretical research in the cognitive sciences identified these mental representations of knowledge as components of a way more complex system called mental lexicon, a repository of knowledge apt at information acquisition, processing, and use [21]. The recent adoption of network science tools has shown how the large-scale, associative structure of word knowledge in the mental lexicon is highly informative of a wide variety of cognitive processes such as lexical processing [19,22,23,24], learning and cognitive development [25,26,27], text structuring and writing styles [28,29,30,31], creativity [32,33], and expertise levels in specific domains [34,5]. Analogously, forma mentis networks act as approximated reconstructions on the mental constructs built by individuals in their associative mental lexicon, representing their perceptions of the outer world [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…(Brennan et al 2013). These results, which suggest that the phonological mental lexicon undergoes a restructuring for first language (L1) speakers of languages that use alphabets, help to understand why Mandarin second language (L2) speakers of English would similarly show evidence of segmentation in speech production tasks (Neergaard, Luo, and Huang 2019;Verdonschot et al 2013). found evidence to support the influence of orthography on phonology within a verbal fluency task in which participants produced as many phonological neighbors to a given Mandarin monosyllable as possible within 1 minute.…”
Section: Introductionmentioning
confidence: 61%
“…Phonological neighborhood measures have long been shown to influence lexical processing. While research on the effects of phonological neighbors has primarily taken place with English and Spanish speakers (For a review, see Vitevitch & Luce, 2016), a recent focus has looked to Mandarin (Neergaard, Britton, et al 2019;Neergaard, Luo, et al 2019;Wiener and Turnbull 2016).…”
Section: Phonological Neighborhood Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…strength of association between words, based on for example their semantic relatedness, is represented by the edge. Different tasks have been used to estimate the networks included in the mental lexicon, for example association tasks (Kenett, Anaki, & Faust, 2014), phonological neighbor tasks (Neergaard, Luo, & Huang, 2019), and semantic verbal fluency tasks (Borodkin et al, 2016b;Kenett, Beaty, Silvia, Anaki, & Faust, 2016;Kenett et al, 2013). In semantic verbal fluency tasks participants are asked to name as many words as possible from a specific category (for example animals) within a time limit (often one minute).…”
mentioning
confidence: 99%